A qualitative investigation of treatment components for families of youth who have sexually offended. Issue 2 (3rd May 2016) - Yoder, Jamie; Ruch, Donna
ABSTRACT: Traditional treatment approaches for youth who commit sexual crimes are generally understudied and lack consideration for youths' evolving context and development. A holistic model is important in service delivery, whereby multiple socio-ecological risk and protective factors are targeted in treatment. Family treatment, a key component of holistic practices, has not been well-defined for families of youth who have committed sexual crimes. Better understanding of the practical techniques used in service agencies can inform family services for youth. Using an inductive grounded theory approach, this qualitative study interviews service providers ( N = 19) to understand components of family treatment. Findings suggest components including problem solving, communication skills, and working through the pain meet certain goals of restructuring and uniting families. The therapeutic relationship was a component that meets all goals of family treatment and helps families and youth overcome stigma of sexual offending. Findings have implications for developing and testing models of family treatment for sexually abusive youth.